Charged particle diagnostic system for lithium ultracold plasma experiments - Saakyan Sergey; Klimov Stepan; Nazarov Alexander; Sautenkov Vladimir; Zelener Boris (E3S Web of Conferences, 2023)
Charged particle detection systems are widely used in modern atomic physics experiments. In this paper we describe an experimental setup for ultracold plasma (UCP) diagnostics based on the basis of a microchannel plate-based detector (MCP). Two different readout techniques for the MCP output are described in detail. Expansion of the low-density UCP and the frequency-dependent response of the UCP to an external electric field are measured. Preliminary results are obtained.